A Nemzeti Hadsereg csendőralakulatai : 1919-1921 - Suba, János (Közép-Európai Közlemények, 2015)
The study reviews those formations that were called gendarme, reserve gendarme, border gendarme, civilian reserve gendarme, supplementary gendarme between 1919 and 1921. The formations were hidden behind these names from the Entente Mission and the occupying Roman headquarters. These formations were under the control of the National Army, where they completed different tasks in connection with public safety and police force. The real number of the armed forces exceeded the permitted one. The study investigates the size and the location of these formations. It describes the organization and development of the National Army, and the reorganizing of the military public administration. These formations existed from the organizing of the Hungarian military forces until the peace treaty of Trianon came into force. In 1921 the size of the military forces was set according to the peace treaty. The remaining formations were given over to the Ministry of Interior.